Study on The Wandering Weekday Effect In The Indonesian Capital Market Based On Trend Moderation Effect - Usman Arief (Riset Akuntansi dan Keuangan Indonesia)
This study investigates a wandering weekday effect, an assumption anomaly from fixed weekday effect to changes over time, under the moderation effect of market trend. We employ daily price data from the Jakarta Stock Exchange (JKSE) from 2000 to 2019. This study reveals that the fixed weekday effect has diminished when we introduced a market trend. Using robustness of distribution error, our further studies find that there is a negative wandering Monday effect when the market is falling. The findings provide a crucial contribution to market efficiency and help to reconcile mixed findings in previous studies.